ARE C‐REACTIVE PROTEIN AND FERRITIN LEVELS BEING OVERLOOKED IN INDIGENOUS AUSTRALIANS WITH CHRONIC KIDNEY DISEASE?. Issue 3 (14th June 2013) - Claes, Jamin; Ellis, Joy‐Anne L.; Rettie, Fiona; Butcher, Belinda; Bradley, Jennifer
SUMMARY Background Indigenous Australians have significantly higher rates of end‐stage renal disease and worse health outcomes than non‐indigenous Australians. Objectives We investigated whether the effect of inflammation on C‐reactive protein (CRP) and ferritin levels is being overlooked in indigenous patients with chronic kidney disease. Design Data for 23, 000 patients were extracted from the Renal Anaemia Management database for the period November 1999 to October 2010. Measurement Haemoglobin, ferritin, transferrin saturation and CRP levels for indigenous and non‐indigenous Australians were compared with target levels given in the Caring for Australians with Renal Impairment (CARI) guidelines. Results Compared with non‐indigenous patients, indigenous Australians had higher median CRP and mean ferritin levels, lower mean haemoglobin level and were less likely to meet CARI targets. Conclusion The effect of inflammation on laboratory parameters should be considered particularly when treating indigenous Australians.